The n-player Hirshleifer contest - Christian Ewerhart; Guang-Zhen Sun (University of Zurich, Department of Economics, 2022)
While the game-theoretic analysis of conflict is often based upon the assumption of multiplicative noise, additive noise such as assumed by Hirshleifer (1989) may be equally plausible depending on the application. In this paper, we examine the equilibrium set of the n-player difference-form contest with heterogeneous valuations. For high or intermediate levels of noise, the equilibrium is in pure strategies, with at most one player being active. For small levels of noise, however, we find a variety of equilibria in which some but not necessarily all players randomize. In the case of homogeneous valuations, we obtain a partial uniqueness result for symmetric equilibria. As the contest becomes increasingly decisive, at least two contestants bid up to the valuation of the second-ranked contestant, while any others ultimately drop out. In the limit, equilibria in the Hirshleifer contest converge to equilibria in the corresponding all-pay auction.
Keywords: C72; D72; D74; 330; Difference-form contest; Nash equilibrium; Rent dissipation; All-pay auction